Effects of Time-Restricted Feeding on Energy Balance: A Cross-Over Trial in Healthy Subjects - Bao, Riqiang; Sun, Yingkai; Jiang, Yiran; Ye, Lei; Hong, Jie; Wang, Weiqing (Frontiers in Endocrinology, 2022)
Time-restricted feeding (TRF) has been recently reported as an effective dietary intervention for losing body weight, implying a negative energy balance, without restricting nutrient intake. However, the detailed energy balance alteration caused by TRF remains unclear. This study was a randomized controlled clinical trial using a within-subject cross-over design. Twelve healthy, normal-weighted volunteers (age: 24 ± 2.3 years; BMI: 21.9 ± 1.71 kg/m2; 7 females) were studied under a rigorous control for calorie intakes, physical activities as well as sleep-wake cycle to evaluate the energy balance systematically. Each participant consumed an isocaloric diet within either a 5.5-hour TRF or 11-hour control schedule. All energy intake and excretion were traced and collected and accessed by bomb calorimetry. Energy expenditure and substrates oxidation were monitored in a metabolic chamber. TRF compared with control schedule is associated with a 22.7% increase in fecal energy loss (Δ = 32.25 ± 9.33 Kcal, p = 0.005) and a trend in increasing 14.5 % urine energy loss (Δ = 6.67 ± 3.14 Kcal, p = 0.058) without change energy expenditure. In total, a negative energy balance (Δ = -45.95 ± 19.00 Kcal, p = 0.034), which was equal to -2.6 % of total energy intake, has been observed during TRF interventions. In the meantime, glycemic profiles, heart rate, respiration rate as well as metabolic flexibility were also improved during TRF intervention. Taken together, our findings unravel the mystery of how TRF regulates energy balance, supporting the use of TRF as an alternative dietary strategy for weight loss.